Nyctaginaceae endémicas del Perú - León, Blanca (2006)
The Nyctaginaceae are represented in Peru by eleven genera and 53 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mostly shrubs and herbs. Here we recognize five endemic species, which are found mainly in Tropical Costal Desert and Desert Shrubland regions, between 100 and 2400 m elevation. Apparently, no endemic species of Nyctaginaceae have been recorded within Peru’s protected areas system.